RNA‐binding protein SAMD4A inhibits breast tumor angiogenesis by modulating the balance of angiogenesis program. Issue 9 (16th July 2021) - Zhou, Meicen; Wang, Bing; Li, Hongwei; Han, Jianqun; Li, Ailing; Lu, Wenbao
Abstract: Tumor‐induced angiogenesis is important for further progression of solid tumors. The initiation of tumor angiogenesis is dictated by a shift in the balance between proangiogenic and antiangiogenic gene expression programs. However, the potential mechanism controlling the expression of angiogenesis‐related genes in the tumor cells, especially the process mediated by RNA‐binding protein (RBP) remains unclear. SAMD4A is a conserved RBP across fly to mammals, and is believed to play an important role in controlling gene translation and stability. In this study, we identified the potential role of SAMD4A in modulating angiogenesis‐related gene expression and tumor progression in breast cancer. SAMD4A expression was repressed in breast cancer tissues and cells and low SAMD4A expression in human breast tumor samples was strongly associated with poor survival of patients. Overexpression of SAMD4A inhibited breast tumor angiogenesis and caner progression, whereas knockdown of SAMD4A demonstrated a reversed effect. Mechanistically, SAMD4A was found to specifically destabilize the proangiogenic gene transcripts, including C‐X‐C motif chemokine ligand 5 ( CXCL5 ), endoglin ( ENG ), interleukin 1β ( IL1β ), and angiopoietin 1 ( ANGPT1 ), by directly interacting with the stem‐loop structure in the 3′ untranslated region (3′UTR) of these mRNAs through its sterile alpha motif (SAM) domain, resulting in the imbalance of angiogenic genes expression. Collectively, our results suggest that SAMD4A is a novel breast tumor suppressor that inhibits tumor angiogenesis by specifically downregulating the expression of proangiogenic genes, which might be a potential antiangiogenic target for breast cancer therapy. Abstract : Here, we identified the expression pattern of RNA‐binding protein SAMD4A in breast cancers and its potential role in modulating angiogenesis‐related gene expression. Mechanistically, SAMD4A could suppress breast tumor angiogenesis and metastasis by selectively destabilizing proangiogenic mRNAs by targeting the stem‐loop structure in 3′UTR.